Addressing Contaminants of Emerging Concern in Aquaculture: A Vacuum Membrane Distillation Approach - Claudio Marcos Eugênio Malaghini; Jussara Garcez; Rodrigo Hoff; Alan Ambrosi; Katia Rezzadori (Membranes)
The presence of contaminants of emerging concern (CECs) in agricultural and fisheries water has raised significant environmental and health concerns. Vacuum membrane distillation (VMD) has shown promise as an effective method for removing non-volatile contaminants, such as CECs, from water. This study presents a novel application of a bench-scale VMD unit to treat water from Lagoa da Conceição, Florianópolis, Brazil, using microporous membranes (0.22 µm) under the following optimized conditions: 75 °C, a flow rate of 24 L·h−1, and a vacuum pressure of −640 mmHg. The system demonstrated remarkable performance in removing several key antimicrobials, including sulfamethoxazole, ciprofloxacin, azithromycin, and clindamycin (500 μg·L−1), with rejection rates of 99.1%, 98%, 99.9%, and 99%, respectively, and an average flux of 7.08 L·m−2·h−1. Additionally, the VMD unit achieved a substantial 99.98% salt rejection. Ecotoxicity tests revealed low toxicity for sulfamethoxazole, ciprofloxacin, and azithromycin but high toxicity for clindamycin, while human risk assessment indicated moderate-to-high risks for ciprofloxacin and clindamycin. The findings highlight the potential of VMD as an effective and sustainable technology for the removal of CECs and biocompounds, enhancing water safety and reducing environmental hazards. This study offers a promising solution for addressing water contamination on a broader scale.